A Novel Graphene Oxide Wrapped Na2Fe2(SO4)3/C Cathode Composite for Long Life and High Energy Density Sodium‐Ion Batteries. Issue 27 (6th August 2018) - Chen, Mingzhe; Cortie, David; Hu, Zhe; Jin, Huile; Wang, Shun; Gu, Qinfen; Hua, Weibo; Wang, Enhui; Lai, Weihong; Chen, Lingna; Chou, Shu‐Lei; Wang, Xiao‐Lin; et al.
Abstract: The cathode materials in the Na‐ion battery system are always the key issue obstructing wider application because of their relatively low specific capacity and low energy density. A graphene oxide (GO) wrapped composite, Na2 Fe2 (SO4 )3 @C@GO, is fabricated via a simple freeze‐drying method. The as‐prepared material can deliver a 3.8 V platform with discharge capacity of 107.9 mAh g −1 at 0.1 C (1 C = 120 mA g −1 ) as well as offering capacity retention above 90% at a discharge rate of 0.2 C after 300 cycles. The well‐constructed carbon network provides fast electron transfer rates, and thus, higher power density also can be achieved (75.1 mAh g −1 at 10 C). The interface contribution of GO and Na2 Fe2 (SO4 )3 is recognized and studied via density function theory calculation. The Na storage mechanism is also investigated through in situ synchrotron X‐ray diffraction, and pseudocapacitance contributions are also demonstrated. The diffusion coefficient of Na + ions is around 10 −12 –10 −10.8 cm 2 s −1 during cycling. The higher working voltage of this composite is mainly ascribed to the larger electronegativity of the element S. The research indicates that this well‐constructed composite would be a competitive candidate as a cathode material for Na‐ion batteries. Abstract : A novel high energy density cathode material for sodium‐ion batteries is synthesized via a facile freeze‐drying process. The Fe 2+ /Fe 3+ redox couple in the alluaudite‐type framework possesses a 3.8 V voltage versus Na/Na + with discharge capacity of 107.9 mAh g −1 as well as capacity retention above 90% after 300 cycles. Investigations of the structural evolution and kinetics are also carried out.